Pegasus : the flame of Olympus - O'Hearn, Kate (Aladdin, 2012)
Reborn as the Flame, thirteen-year-old Emily has saved Olympus from destruction but when the gruesome Nirads begin a new invasion, Emily and her friends become entangled in the conflict as old grudges are unearthed and new enemies are discovered.